Toward a Common Secure Future: Four Global Commissions in the Wake of Ebola. - Lawrence O Gostin; Oyewale Tomori; Suwit Wibulpolprasert; Ashish K Jha; Julio Frenk; Suerie Moon; Joy Phumaphi; Peter Piot; Barbara Stocking; Victor J Dzau; Gabriel M Leung (PLoS Medicine)
Lawrence Gostin and colleagues offer a set of priorities for global health preparedness and response for future infectious disease threats.